A Modeling Framework for Computing Lifetime and Information Capacity in Wireless Sensor Networks - DUARTE-MELO, Enrique (Institutional Knowledge at Singapore Management University, 2004)
In this paper we investigate the expected lifetime and information capacity, defined as the maximum amount of data (bits) transferred before the first sensor node death due to energy depletion, of a data-gathering wireless sensor network. We develop a fluidflow based computational framework that extends the existing approach, which requires precise knowledge of the layout/deployment of the network, i.e., exact sensor positions. Our method, on the other hand, views a specific network deployment as a particular instance (sample path) from an underlying distribution of sensor node layouts and sensor data rates.